Field Reporting on the Working of Community Listening Scheme - Planning Commission (Planning Commission, 1969)
To meet the increasing demand for evaluation studies, P..E..O. decided to take up under the programme of periodical field r porting, short—term evaluation of such programmes which did not call for intensive depth studies. The evaluation of the Community Listening Scheme is the first study taken up under this programme at the instance of the Ministry of Information and Broadcasting.
Programme Evaluation Organisation Planning Commission Government of India